PENGARUH PENERAPAN CORPORATE GOVERNANCE TERHADAP EARNINGS MANAGEMENT DALAM PERUSAHAAN PERBANKAN DI INDONESIA - Maulidah, Diana (Jurnal Akuntansi AKUNESA, 2014)
This study investigated the effect of implementation of corporate governance on earnings management in corporate banking in Indonesia to understand about corporate governance by using the proxy of corporate governance, namely: (1) stakeholders, (2) the board of commissioners, (3) directors, (4) internal auditors, (5) external auditor, (6) audit committee, (7) compliance officer, (8) company secretary, and (9) sharia supervisory board, banking corporate governance and earnings management, explain sense of agency theory, signaling theory, shareholder theory, and contingency theory, know the health of banks in Indonesia with Risk approach and substance use settings. Keywords: Corporate Governance, Earnings Management, Indonesian Banking.